Significance of Flexible Substrates for Wearable and Implantable Devices: Recent Advances and Perspectives. Issue 3 (2nd November 2021) - Hassan, Muhammad; Abbas, Ghulam; Li, Ning; Afzal, Annum; Haider, Zeeshan; Ahmed, Saad; Xu, Xiuru; Pan, Caofeng; Peng, Zhengchun
Abstract: In the past decade, flexible electronics have attracted significant research attention due to their distinct features and emerging applications in numerous fields such as, flexible displays, implantable sensors, and energy storage systems, among other applications. Due to the development of flexible electronics, this paper details the substrates employed to produce flexible electronic devices, given that substrates generally govern the overall device properties. The increase in research attention can be attributed to the use of films as flexible substrates, which enable the implementation of numerous design strategies and engineering methodologies, thus leading to extensive advances in the manufacturing quality and prospect of flexible electronics in various applications. This paper provides a comprehensive review of the significance of substrates in flexible wearable electronics over the past decade, such as, the substrate properties requirements, processing classification, important flexible devices, and applications, including sensing, energy storage, and other electronic devices. Abstract : Flexible substrates play a vital role in wearable and implantable electronics. The selection and integration of substrate technology with suitable features are crucial, further enable the implementation of numerous design strategies and engineering methodologies, leading to extensive advances in manufacturing quality and promising the future growth of flexible electronics in many applications including wearable sensors, implantable electrodes, and others.